2015
DOI: 10.1002/ajhb.22735
|View full text |Cite
|
Sign up to set email alerts
|

Is the area of the orbital opening in humans related to climate?

Abstract: These data may support the hypothesized association between size of the orbital opening and adaptation to different climatic conditions, but only in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Franciscus and Long (72), Roseman (79), Noback et al, (78) and Tomaszewska et al (83) suggest that climate affects cranial morphology, suggesting in particular that face shape is reflective of temperature variation. Nutrition and socioeconomic status have also been suggested to affect bone morphology and levels of sexual dimorphism (12,(85)(86)(87)(88)(89)(90)(91).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Franciscus and Long (72), Roseman (79), Noback et al, (78) and Tomaszewska et al (83) suggest that climate affects cranial morphology, suggesting in particular that face shape is reflective of temperature variation. Nutrition and socioeconomic status have also been suggested to affect bone morphology and levels of sexual dimorphism (12,(85)(86)(87)(88)(89)(90)(91).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the functional constraints of childbirth and sexual selection forces involved in the evolution of cranial traits, environmental variables may also have a role in either os coxae or cranium shape. Climate has been proposed to affect both pelvic and cranial morphology . For example, Ruff and Betti et al show that bi‐iliac breadth varies between populations of different latitudes given eco‐geographic principles.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, temperature diversity showed a strong signature on postcranial anatomy, associated mainly to body size (Auerbach, ; Ruff, ), limb proportions (Béguelin, ; Holliday, ; Pearson, ), and hand and foot proportions (Betti, Lycett, von Cramon‐Taubadel, & Pearson, ). Nevertheless, cranial structures such as the cranial vault (Katz et al, ; Pan et al, ), facial skeleton size (Bernal et al, ; Hubbe, Hanihara, & Harvati, ), facial skeleton shape (Evteev, Cardini, Morozova, & O'higgins, ; Harvati & Weaver, ), temporal bone size (Smith, Terhune, & Lockwood, ), orbital area (Tomaszewska, Kwiatkowska, & Jankauskas, ), maxillar and zygomatic bones (Cui & Leclercq, ; Maddux & Butaric, ), and nasal cavity shape (Franciscus & Long, ; Noback et al, ) also showed a significant association with temperature diversity. In general terms, individuals from cold climates have been characterized with larger and more robust skulls than individuals living at warmer temperatures (Beals, Smith, & Dodd, ; Béguelin, ; Hubbe et al, ; Katzmarzyk & Leonard, ; Perez & Monteiro, ; Roseman, ; Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is difficult to disentangle the effects of climate, diet, disease, and inbreeding in most anthropological studies. Recently, Tomaszewska et al [138] suggested that symmetry of the orbital opening may be related to climate, with fluctuating asymmetry transitioning to directional asymmetry as one travels from warmer to colder climates. Nevertheless, the degrees of freedom in this study are inflated by the pooling of 846 skulls from several populations across Europe into three categories-warm, temperate, and cold.…”
Section: Climatementioning
confidence: 99%